Kelah sang demang Jahja Datoek Kajo : Pidato otokritik di Volkstraad 1927-1939 / Azizah Etek, Mursyid, A.M. dan Arfan B. Razif. - AZIZAH ETEK; Mursyid A.M.; Arfan B. Razif (LKiS, 2008)
xvi, 512 hlm. ilus. ; 21 cm (3 eks.)